A high strength alumina-silicon carbide-boron carbide triplex ceramic. Issue 10 (July 2017) - Neuman, Eric W.; Hilmas, Gregory E.; Fahrenholtz, William G.
Abstract: A ceramic particulate composite composed of oxide, and carbide ceramics was found to have high strength, hardness, and fracture toughness values. A composition consisting of Al2 O3 with 15 vol% SiC and 15 vol% B4 C additions was produced by hot-pressing at 1650 °C for 30 min, with full density reached after ~5 min at temperature. Both WB and WB2 were observed, with the W source presumably an impurity from WC milling media, and Al18 B4 O33 was also detected following densification. Strength was ~880 MPa, which is greater than values reported for comparable composites of Al2 O3 containing 30 vol% SiC or B4 C. Vickers hardness was ~21 GPa, and fracture toughness was ~4.5 MPa m ½, comparable to values reported for the binary mixtures. The calculated critical flaw size of the material was similar to the size of the SiC/B4 C clusters and microcracking at grain boundaries. The latter resulting from thermal expansion mismatch between the Al2 O3 matrix and SiC/B4 C reinforcing phases.